(untitled) (Italian Journal of Public Health, 2012)
The vaccination rate in several European coun- tries among healthcare personnel is still less than 25% (1), despite many international health authorities widely recommend annual flu vaccina- tion of healthcare workers as the best way to pre- vent the disease and to avoid the transmission of influenza from staff to patients.